Rapid antibody conformational screening by matrix‐assisted laser desorption/ionization hydrogen‐deuterium exchange mass spectrometry. Issue 12 (16th February 2022) - Mukherjee, Debopreeti; Trigo‐Mouriño, Pablo; Jiang, Yuan; Nowak, Timothy; Shchurik, Vladimir; Adpressa, Donovon A.; Louie, Michael T.; Reynolds, Shane R.; Hohn, Michael J.; Al‐Sayah, Mohammad Ahmed; Pirrone, Gregory F.; Makarov, Alexey A.
Abstract : Recent advances in the field of cancer biology have accelerated the discovery and development of novel biopharmaceuticals. At the forefront of these drug development efforts are high‐throughput screening, compressed timelines, and limited sample quantities, all characteristic of the discovery space. To meet program targets, large numbers of protein variants must be produced, screened, and characterized, presenting a daunting analytical challenge. Additionally, the higher‐order structure is paramount for protein function and must be monitored as a critical quality attribute. Matrix‐assisted laser desorption/ionization mass spectrometry has been utilized as an ultra‐fast, automatable, sample‐sparing analytical tool for biomolecules. Our group has published applications integrating hydrogen‐deuterium exchange mass spectrometry with matrix‐assisted laser desorption/ionization mass spectrometry for the rapid conformational characterization of small proteins, the current work expands this application to monoclonal and bi‐specific antibodies. This study demonstrates the ability of the methodology, matrix‐assisted laser desorption/ionization hydrogen‐deuterium exchange mass spectrometry, to detect conformational differences between bi‐specific antibodies from different expression hosts. These conformational differences were validated by orthogonal techniques including circular dichroism, nuclear magnetic resonance, and size‐exclusion chromatography hydrogen‐deuterium exchange mass spectrometry. This work demonstrates the utility of applying the developed methodology as a rapid conformational screening tool to triage samples for further analytical characterization.